The conception and exploration of the underwater vehicle simulator. Issue 1 (July 2021) - Shao-feng, Gong; Jian-bin, Zhang; Dong, Cheng; Hai-Yan, Xiao; Ping, Dong; Zhan-sheng, WU
Abstract: In this paper, a new type of underwater vehicle simulator is proposed. The underwater vehicle simulator adopts capsule prefabrication structure and can be carried on UUV Each UUV can be loaded with multiple underwater vehicle simulator capsules. After sailing to the predetermined location, long-distance delivery is carried out. After the underwater vehicle simulator is fully charged and expanded, the underwater vehicle simulator cluster is formed to achieve tactical purposes such as confusing and inducing enemies in quantity, orientation and deployment. The technology can be applied to the new generation of underwater vehicle safety defense system, and can be popularized and applied to other weapon systems. It has great military, political and national defense significance and has broad application prospects.